IL-4 receptor engagement in human neutrophils impairs their migration and extracellular trap formation - Impellizzieri, Daniela; Ridder, Frederike; Raeber, Miro E.; Egholm, Cecilie; Woytschak, Janine; Kolios, Antonios G.A.; Legler, Daniel F.; Boyman, Onur (Journal of allergy and clinical immunology, 2019)
Type 2 immunity serves to resist parasitic helminths, venoms, and toxins, but the role and regulation of neutrophils during type 2 immune responses are controversial. Helminth models suggested a contribution of neutrophils to type 2 immunity, whereas neutrophils are associated with increased disease severity during type 2 inflammatory disorders, such as asthma. We sought to evaluate the effect of the prototypic type 2 cytokines IL-4 and IL-13 on human neutrophils. Human neutrophils from peripheral blood were assessed without or with IL-4 or IL-13 for (1) expression of IL-4 receptor subunits, (2) neutrophil extracellular trap (NET) formation, (3) migration toward CXCL8 in vitro and in humanized mice, and (4) CXCR1, CXCR2, and CXCR4 expression, as well as (5) in nonallergic versus allergic subjects. Human neutrophils expressed both types of IL-4 receptors, and their stimulation through IL-4 or IL-13 diminished their ability to form NETs and migrate toward CXCL8 in vitro. Likewise, in vivo chemotaxis in NOD-scid-Il2rg−/− mice was reduced in IL-4–stimulated human neutrophils compared with control values. These effects were accompanied by downregulation of the CXCL8-binding chemokine receptors CXCR1 and CXCR2 on human neutrophils on IL-4 or IL-13 stimulation in vitro. Ex vivo analysis of neutrophils from allergic patients or exposure of neutrophils from nonallergic subjects to allergic donor serum in vitro impaired their NET formation and migration toward CXCL8, thereby mirroring IL-4/IL-13–stimulated neutrophils. IL-4 receptor signaling in human neutrophils affects several neutrophil effector functions, which bears important implications for immunity in type 2 inflammatory disorders. [Display omitted]